(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze the association between chronic exposure to pesticides and the development of hematological cancers in a region with intense agricultural activity. This is a hospital-based case-control study. Socioeconomic, demographic, occupational and health-related aspects of patients were investigated. The univariate odds ratio (OR) of cases was verified using logistic regression analysis. In the multivariate analysis, the relevant variables in the model were maintained (p = 0.05). There was a predominance of males in the case (54.0%) and control (53.0%) groups. The mean age was 58.8 ± 14.5 years in the case group and 55.6 ± 12.9 years in the control group. It was found that 38.7% of the cases were farmers, and that contact for more than five years with pesticides increases the chances of developing hematological cancers by 2.19 times (OR = 2.19; 95% CI 1, 19 - 4.06). It was also found that the higher the family income, the lower the chances of these neoplasms to appear (OR = 0.26; 95% CI 0.11 - 0.65). In addition, patients who did not have a family history of cancer were 96% less likely (OR = 0.04; 95% CI 0.02 - 0.08) to develop the disease. Chronic exposure to pesticides, family history of cancer and socioeconomic status are associated with greater chances of developing hematological neoplasms. Rural workers exposed to these substances for periods of more than five years are more vulnerable.